The occurrence of liver steatosis in patients with chronic hepatitis C - the experience of the Clinical Center of Vojvodina - Preveden, Tomislav; Ružič, Maja; Kovačević, Nadica; Pete, Maria; Fabri, Milotka (Vojnosanitetski pregled, 2021)
AbstractBackground/ Aim. Hepatic steatosis in individuals with chronic hepatitis C occurs in about half of cases. Its occurrence is influenced by factors of the host and viral factors, and its importance lies in the fact that it reduces the success of antiviral therapy based on interferon in the treatment of chronic hepatitis C and that, associated with other factors, exacerbates liver disease. The objective this paper is to determine the prevalence and severity of steatosis in patients with chronic hepatitis C and to determine the factors that affect its occurrence. Methods. The research includes 123 patients with chronic hepatitis C, in which the diagnosis of liver steatosis was made by a liver biopsy and histopathological examination according to which ≥5% of hepatocytes is affected by the fatty change. Based on the presence of steatosis, the patients were divided into two groups, 43 patients with steatosis, 80 without steatosis. The influence of certain factors on the occurrence of steatosis was examined using standard statistical methods. Results. Liver steatosis was found in 34.96% of subjects with chronic hepatitis C, and most patients had mild steatosis 76.74%. Of the examined predictive factors for the occurrence of steatosis, statistical significance in its occurrence belongs to elevated BMI, genotype 3HCV, and HCV viremia. Conclusion. Hepatic steatosis often occurs in people with chronic hepatitis C, and it is most often mild. The occurrence of hepatic steatosis in our sample was most affected by genotype 3 HCV and HCV viremia level. Hepatic steatosis can reduce the success of antiviral therapy based on interferon and worsen chronic liver disease course. Therefore, we need to recognize it, treat it and remove it.
Keywords: fatty liver; hepatitis c; risk factors; genotype; hepacivirus; body mass index.